Management for scientists - Mellor, Robert B. (Bingley, U.K. : Emerald Publishing Limited, 2019)
Scientific progress - from creating better medicines to building better bridges or designing improved technology networks - can lead to intriguing business opportunities, but business expertise is not always a natural companion to scientific excellence. Scientists require a nuanced understanding of the modern business environment to successfully navigate the commercial world and maximise the economic potential of their ideas. Management for Scientists explores the core theories and practices in management studies today in a context applicable to those working in the scientific industries. Essential business concepts covered include corporate strategy and business planning, organisation structure, management and operations, and labour and human resources, and these are all viewed through the prism of building, maintaining and developing a scientific business in the pharmaceutical, biotechnology, engineering, maths, and computing sectors. Chapters feature a range of real-world examples from modern science-driven businesses, presented by experienced scientists with demonstrated strategic and economic business expertise.
Prelims -- Chapter 1: Economics, monetary theory and fiscal policy -- Chapter 2: Theory of the firm and the law -- Chapter 3: Entrepreneurship -- Chapter 4: Organizational structures for tech firms -- Chapter 5: Strategy and strategic management -- Chapter 6: Information and knowledge governance -- Chapter 7: Change management: the organization as a micro-macro system -- Chapter 8: Marketing for scientists -- Chapter 9: HR theory and employment law -- Chapter 10: Intellectual property rights (IPRs) -- Chapter 11: Online resources for biologists -- Chapter 12: Management in life sciences -- Chapter 13: Agile methods for engineering -- Index.
Includes index.
Print version record
Keywords: Science -- Vocational guidance; Business planning; Business & Economics -- Management; Management & management techniques